The History Of The Irrigation System In Uzbekistan Analysis of the relationship between some biomechanical variables and motor abilities to perform the backflip skill on the balance beam (Texas Journal of Multidisciplinary Studies, 2024)
Kinematic analysis plays an effective and influential role in applying biomechanical conditions, such as finding the different movement speeds of body parts. These analytical laboratories and other factors related to the physical, technical, and psychological aspects combined have contributed to the development of sports worldwide and the creation of a high-level athlete. The balance beam is one of the devices whose motor skills are characterized by precision and motor balance and whose movements include rotational movements, straight transitional movements, and movements, some of which are performed on the longitudinal axis and the transverse axis and some of them are combined with more than one axis. Such movements are subject to all variables, requiring high motor balance due to their specificity. The crossbar device. To achieve good performance, the athlete must have a high degree of control over her body's movement and the direction of its parts during movement. The research problem is summarised in the presence of a problem that lies in an apparent weakness in the performance of skills that require high balance on the balance beam, as the area of the support base constantly changes. The athlete is often forced to perform her movements, and her centre of gravity is on the verge of falling, as the body’s centre of gravity is off track. The correct posture during performance often loses its balance partially depending on the amount of deviation that occurs, so the researcher investigated and explained this problem because it is a problem worthy of study and because it investigates the reality of the relationships between physical abilities and performance on the one hand and on the other hand the kinematic conditions